El Liderazgo Del Docente Del Bachillerato Como Modelamiento Para Los Estudiantes Adolescentes De La Unidad Educativa Emigdio Esparza Moreno - Altamirano Medina, Bertha Yolanda (2014)
As a requirement in the research master's program whose theme is "Leadership as a teacher of high school students modeling for teens educational unit Emigdio Esparza Moreno", considering that leadership is the result of personal dispositions, qualities and develops attributes of individuals where their ways which is the basis of their teaching can generate constructive or destructive attitudes in students. This study aims to determine the influence of high school teacher leadership in modeling teenage students, the methodology was applied as descriptive and explanatory type, and as the study went to 3 managers, 8 teachers and 188 students, applying a questionnaire to each focus group. The results determined the failure of leadership style on teachers, their passive attitudes or level of manipulation that are not contributing to exert adequate modeling behaviors that assume students. Therefore it is proposed as a viable development plan leadership training for driving change in the model of teaching, it is expected that satisfies the need to change attitudes and behavior of staff at the institution magisteril arises.